IMPLEMENTASI MODEL DISCOVERY LEARNING DALAM UPAYA MENINGKATKAN MINAT EKSPLORASI LINGKUNGAN SOSIAL PADA MATA PELAJARAN SOSIOLOGI DI KELAS XII IPS. 2 SMA NEGERI 6 KOTA BEKASI - Jojor Purba (Jurnal Dinamika Pendidikan, 2015)
This Classrooms Action Research (CAR) was conducted to determine the application of the discovery learning in the learning process as well as to find out the increment interest in the exploration of the social environment of grade XII.IPS.2 students of SMA 6 Bekasi who were also as the research subject. The activity of students in following the learning process by using Discovery Learning method has increased by 4 aspects of cooperation, liveliness, courage and the percentage / deliver results. Student learning outcomes also increased. From the results of these studies concluded that the implementation of Discovery Learning method improved social environment exploration interests Sociology in subject in Class XII IPS.2 SMAN 6 Bekasi.Keywords : Classroom Action Research, Discovery Learning Method, Sociology